The Roles of Motivation in the English Language Learning - Christianto, Danin; Karin, Ivena (Universitas Negeri Semarang, 2019)
English has become one of the global languages which is used in many fields, including in the field of education. In Indonesia, especially, English is considered as a foreign language which means that this language is not always used in daily lives, only in certain conditions or situations. Considering the issue, the rate of English language learning and practice is still low. In order to learn English, learners require motivation so that they can be successful in learning the language. Therefore, the roles of motivation is very crucial during the teaching and learning process. Previously, some of the researches stated that external or instrumental motivation was the one which drove learners to learn English in countries where this language was considered as a foreign language. The result implicated that motivation which dominated the English language learning process was instrumental motivation. It means that such a motivation was the foundation which encouraged learners to learn English in order to get good scores in schools, get jobs, pass examination, and pursue careers. On the other hand, in countries where English is used as a second language, learners learn English are directly motivated because of the inner needs to learn and develop their English skills. In addition, external factors, like environment and media, also play important roles in motivating learners to learn English.